Mobile Environment for Developing User Situation Awareness (MEDUSA): Training for Healthcare Professionals. (December 2020) - Kass, Steven J.; Eddy, Brian; Reichherzer, Thomas; Van Der Like, Jill; Jones, Dean; King, Alexander; Mazour, Branden; McCourt, Ryan
This paper describes the development of a mobile phone application (MEDUSA) for training situation awareness. MEDUSA was developed as a cost efficient form of on demand training to supplement other more costly, traditional forms of training such as simulation labs and live patient rounds. Users care for a simulated patient and are tested using a version of the Situation Awareness Global Assessment Technique (SAGAT). Users receive feedback on how many SAGAT queries they answered correctly and are provided tips on how to improve SA. Initial usability testing demonstrated strong support for the program among a sample of nursing students. Continued efforts are on-going in the design and testing of a teaching portal that allows trainers to easily create their own scenarios.